2021
DOI: 10.1002/lt.25962
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Stimulate Liver Regeneration in a Rat Model of Partial Liver Transplantation

Abstract: Living donor liver transplantation (LDLT) is sometimes associated with impaired regeneration and severe ischemia/reperfusion injury (IRI) in the graft, resulting in small-for-size syndrome (SFSS). Platelets were previously reported to stimulate liver regeneration in models of hepatectomy, but the evidence in partial liver transplantation (LT) is lacking. In this study, a rat model of partial LT was used, and the impact of thrombopoietin (TPO)-induced perioperative thrombocytosis on graft regeneration, IRI, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Additionally, other innate immune cells, including NKT cells, especially the Valpha14 NKT cell subtype, have been recognized for their role in immune tolerance following infusion 208 . In IRI, platelets are influenced by the inflammatory mediators released by KCs, resulting in the release of IL‐6, platelet‐activating factors, growth factors, TGF‐β, and other cytokines that contribute to the advancement of inflammation 209–211 . Peritoneal macrophages with the F4/80 hi GATA6 + LMP phenotype have been observed to migrate to the injury site and contribute to liver repair in experimental models of acute liver injury 212 …”
Section: Immune Effects In Liver Irimentioning
confidence: 99%
“…Additionally, other innate immune cells, including NKT cells, especially the Valpha14 NKT cell subtype, have been recognized for their role in immune tolerance following infusion 208 . In IRI, platelets are influenced by the inflammatory mediators released by KCs, resulting in the release of IL‐6, platelet‐activating factors, growth factors, TGF‐β, and other cytokines that contribute to the advancement of inflammation 209–211 . Peritoneal macrophages with the F4/80 hi GATA6 + LMP phenotype have been observed to migrate to the injury site and contribute to liver repair in experimental models of acute liver injury 212 …”
Section: Immune Effects In Liver Irimentioning
confidence: 99%
“…LSECs and KCs were also reported to interact with platelets to stimulate liver regeneration. It was identified that platelets induced the release of IL-6 from LSECs through direct contact with LSECs[ 61 ]. On the other hand, platelets could attach to KCs, and the hepatic expression of TNF-α and IL-6, which are predominantly produced by KCs, increased in response to the interaction between platelets and KCs[ 62 ].…”
Section: Evidence From Basic Studiesmentioning
confidence: 99%
“…Although the positive role of higher perioperative platelet counts has been suggested, the precise mechanisms clarifying how platelets interact with other cells under I/R conditions were reported recently. Liang et al [ 61 ] reported that TPO-induced preoperative thrombocytosis contributed to a better outcome in a rat model of partial LT. In this study, platelets stimulated liver regeneration after partial LT via several proliferation-related cytokines and pathways.…”
Section: Evidence From Basic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both models are representative of findings in patients. The partial hepatectomy model simulates natural progression after hepatectomy surgery in patients with various liver diseases and explores novel therapeutic measures and enhance the recovery after hepatectomy, but also provide a more effective and safe guidance program for living donor liver transplantation ( Nojima et al, 2016 ; Liang et al, 2021 ). The CCl4 model simulates conditions for patients subjected to toxins, to radiation or having viral infections that target the pericentral (polyploid) cells.…”
Section: Mouse Models Of Acute Liver Injurymentioning
confidence: 99%